Window contamination on Expose-R. Issue 1 (January 2015) - Demets, R.; Bertrand, M.; Bolkhovitinov, A.; Bryson, K.; Colas, C.; Cottin, H.; Dettmann, J.; Ehrenfreund, P.; Elsaesser, A.; Jaramillo, E.; Lebert, M.; van Papendrecht, G.; et al.
Abstract Expose is a multi-user instrument for astrobiological and astrochemical experiments in space. Installed at the outer surface of the International Space Station, it enables investigators to study the impact of the open space environment on biological and biochemical test samples. Two Expose missions have been completed so far, designated as Expose-E (Rabbow et al. 2012) and Expose-R (Rabbow et al. this issue). One of the space-unique environmental factors offered by Expose is full-spectrum, ultraviolet (UV)-rich electromagnetic radiation from the Sun. This paper describes and analyses how on Expose-R, access of the test samples to Solar radiation degraded during space exposure in an unpredicted way. Several windows in front of the Sun-exposed test samples acquired a brown shade, resulting in a reduced transparency in visible light, UV and vacuum UV (VUV). Post-flight investigations revealed the discolouration to be caused by a homogenous film of cross-linked organic polymers at the inside of the windows. The chemical signature varied per sample carrier. No such films were found on windows from sealed, pressurized compartments, or on windows that had been kept out of the Sun. This suggests that volatile compounds originating from the interior of the Expose facility were cross-linked and photo-fixed by Solar irradiation at the rear side of the windows. The origin of the volatiles was not fully identified; most probably there was a variety of sources involved including the biological test samples, adhesives, plastics and printed circuit boards. The outer surface of the windows (pointing into space) was chemically impacted as well, with a probable effect on the transparency in VUV. The reported analysis of the window contamination on Expose-R is expected to help the interpretation of the scientific results and offers possibilities to mitigate this problem on future missions – in particular Expose-R2, the direct successor of Expose-R.